The Role of Perceived Organisational Support in Predicting Organisational Commitment and Organizational Citizenship Behavior in Professional Organizations - Singh, Sandhya; Dias, Rui; Irfan, Mohammad; Galvão, Rosa; Alexandre, Paulo; Gonçalves, Sidalina (Journal of Ecohumanism, 2024)
The study examined the "role of perceived organisational support in predicting organisational commitment and organisational citizenship behaviour in professional organisations". The primary data was acquired through a questionnaire from 200 respondents (employees from the finance and technology sectors) via a stratified random sampling technique. Excel and SPSS 26 were utilised for data analysis, and Statistical tools such as Anova, regression and correlation were used. The results demonstrated that perceived organisational support (POS) positively influences organisational commitment. Moreover, it has been found that perceived organisational support (POS) and organisational citizenship behaviour (OCB) in professional organisations have a substantial correlation, and there are significant differences in the perception of organisational support, commitment, and OCB among professionals working in the technology and finance sectors. This study can assist decision-makers and managers in the finance and technology sector in creating a comprehensive plan for organisational support and development programs that effectively include employees in their job responsibilities. The study provides valuable insights into the importance of perceived organisational support in fostering organisational commitment and citizenship behaviour.